The effect of sintering temperature on the mechanical properties of ceramic. Issue 1 (January 2021) - Ismiati, N; Darwis, D
Abstract: The purpose of this research is to utilize natural resources in the form of clay and white sand in ceramics formation and to determine the effect of sintering temperature on the mechanical properties of the ceramics (compressive strength, thermal shrinkage and porosity) made from clay and silica sand (SiO2 ) with a temperature variations. Ceramic formation used a mixture of clay and silica sand (SiO2 ) with a ratio of 70%: 30%, then mold and compacted them using a hydraulic press to a pressure of 5 Mpa. The samples were then heated in a furnace at temperatures of 700°C, 800°C and 900°C for 3 hours. The results of the calculation of mechanical properties show that all samples meet SNI standards and the ceramic that has the best quality is the ceramic sintered at a temperature of 900°C because it has the highest compressive strength, low thermal shrinkage and low porosity of 21.09 Mpa, 0.680% and 17.92 %, respectively.